Perlindungan Hukum terhadap Korban Penyebaran Video Porno di Social Mendia “Telegram” - Fitriyani, Emilia (Proceedings Series on Social Sciences & Humanities, 2024)
The spread of pornographic content on social media, including Telegram, has become an increasingly urgent issue that needs to be addressed legally.this research aims to explore the legal framework that can protect victims from the distribution of pornographic videos on the Telegram platform the research methods used are document analysis and case studies to understand the implementation of relevant laws in this context.research findings show that legal protection for victims of spreading pornographic videos on Telegram is still limited and requires more attention from the authorities.the implication of this research is the need for improved policies and more effective law enforcement to protect victims and prevent the spread of pornographic content on social media.